Individual and combined associations of body mass index and waist circumference with components of metabolic syndrome among multiethnic middle-aged and older adults: A cross-sectional study - Yang, Mei; Zhang, Yan; Zhao, Wanyu; Ge, Meiling; Sun, Xuelian; Zhang, Gongchang; Dong, Birong (Frontiers in Endocrinology, 2023)
Objectives: Obesity is a major risk factor for metabolic syndrome. Numerous studies evaluate metabolic syndrome and its components using BMI or WC, but not both. Researches on the association of combined effects of BMI and WC with the components of metabolic syndrome are relatively lacking. Therefore, we investigated the individual and combined associations of BMI and WC with components of metabolic syndrome and explored whether age, sex and ethnicity affected the aforementioned associations. Methods: A total of 6,298 middle-aged and older adults were included. Based on the BMI and WC, the participants were divided into comorbid obesity, abdominal obesity alone, general obesity alone and non-obese subgroups. Metabolic syndrome was evaluated using the criteria recommended by the Chinese Diabetes Society. Poisson regression models with robust variance were used to evaluate the associations of obesity types with individual component of metabolic syndrome. And interaction test was conducted to explore whether age, sex and ethnicity affect the aforementioned associations. Results: Compared with reference group (comorbid obesity), individuals in other 3 groups showed decreased prevalence of fasting hyperglycemia (PR=0.83, 95% CI=0.73–0.94 for abdominal obesity alone, PR=0.60, 95% CI=0.38–0.96 for general obesity alone and PR=0.46, 95% CI=0.40–0.53 for non-obese group), hypertension (PR=0.86, 95% CI=0.82–0.90 for abdominal obesity alone, PR=0.80, 95% CI=0.65–0.97 for general obesity alone and PR=0.69, 95% CI = 0.66–0.73 for non-obese group), and hypertriglyceridemia (PR=0.88, 95% CI=0.82–0.95 for abdominal obesity alone, PR=0.62, 95% CI=0.47–0.81 for general obesity alone and PR=0.53, 95% CI=0.49–0.57 for non-obese group). However, participants in abdominal obesity alone and non-obese group had decreased prevalence of low HDL-C level while participant in general obesity alone did not (PR=0.65, 95% CI=0.41–1.03, p>0.05). Besides, the aforementioned associations were not affected by age, sex and ethnicity (all p for interactions>0.05). Conclusions: Comorbid obesity is prior to general and abdominal obesity in detecting the individual component of metabolic syndrome in middle-aged and older adults. And the aforementioned associations were not affected by age, sex and ethnicity. Great importance should be attached to the combined effect of BMI and WC in clinical practice.